Is step-cut shortening osteotomy a better choice than transverse osteotomy for total hip arthroplasty for crowe type iii-iv hip dysplasia? - Turgut, Necmettin; Erdem, Mehmet; Erdem, Ahmet Can; Bayam, Levent; Batar, Suat; Sağlam, Necdet; Gülabi, Deniz (My University, 2024)
Introduction: Total hip arthroplasty for developmental hip dysplasia is a challenging surgery due to anatomic abnormalities. Crowe III and Crowe IV hip dysplasia generally necessitates a subtrochanteric shortening osteotomy. Transverse and step-cut osteotomy are the most common procedures for shortening of femur although there is still no consensus which one is a superior method. The objective of this study was to demonstrate whether transverse or step-cut osteotomy is superior in hips who undergo arthroplasty for high riding hip dysplasia. Hypothesis: Our hypothesis was that higher rates of union would be achieved in patients with Crowe III-IV hip dysplasia when the step-cut osteotomy was performed compared to transverse osteotomies. Material and methods: A total of 99 hips from 90 patients (9 bilateral, 81 unilateral; 79 female, 11 male), each with a minimum follow-up duration of two years, were included in this study. The hips were classified as Crowe III (n = 16) or IV (n = 83). All hips were implanted cementless. Transverse or step-cut osteotomy was chosen for osteotomy type. The clinical and functional outcomes were assessed using the Harris Hip Score (HHS), limb length discrepancy (LLD), and limping. The complications and management of these were noted. The union rates were compared between osteotomy types. Results: The mean age at surgery was 48.8 (range, 21–79 years). The follow-up period was 64.3 months in average (range, 24 to 192 months). The mean Harris Hip Score before surgery was 35.6 (range, 18–50), and increased to 88.1 (range, 61–98) points at the most recent follow-up. The preoperative leg length discrepancy (LLD) measured 5.3 cm (with a range of 3 to 6.8), while the postoperative LLD reduced to 0.8 cm (with a range of 0 to 1.6). There were a total of 38 complications in 35 patients out of 99 cases, resulting in a complication rate of 38.4%. The most frequent complication observed was intraoperative femoral fractures, occurring in 13 cases. Residual limping was seen in 73.7% of all. Step-cut osteotomy was performed in 64 hips (35 CDH stem [Zimmer Biomet, Warsaw, IN, USA], 29 Wagner Cone stem [Zimmer Biomet, Warsaw, IN, USA]) and, transverse in 35 hips (22 CDH, 13 Wagner Cone). Six hips had nonunion problem and all of them were operated with a step-cut osteotomy (z-score: –7.12 and p < 0.00001, Mann-Whitney U Test). Conclusion: Transverse osteotomy may be a better option while performing a shortening subtrochanteric level osteotomy for total hip arthroplasty for Crowe III-IV hips. Level of evidence: Level III; observational retrospective cohort study.
Keywords: Hip Dysplasia; Step-Cut Osteotomy; Subtrochanteric Shortening Osteotomy; Total Hip Arthroplasty; Transverse Osteotomy